Side-chain effect in ethenylene fused thiophene-vinylene-thiophene (ETVT) based photovoltaic polymers. (22nd March 2019) - Wang, Xiaochen; Tang, Ailing; Chen, Fan; Zhou, Erjun
Abstract: To investigate side chain effect of ETVT based photovoltaic polymers, we designed and synthesized the polymers with different solubilizing substituents. The impact of side chains on the solubility, planarity, optical and electronic properties of these ETVT based conjugated polymers was systematically studied. Extending the intrinsic alkyl group or adding new alkyl substituent to the polymer obviously increased the solubility of the resulting polymers. Thus, the polymerization reaction yield was improved to 88% and 81%, forPETVT-TBT24 andPETVT8-TBT, compared to that of 39% forPETVT-TBT .PETVT8-TBT showed blue-shifted absorption spectrum, reduced hole mobility and consequently inferior photovoltaic performance, owing to the steric hindrance caused by redundant octyl group on ETVT unit. However, the introduction of alkyl substitutes in ETVT remarkably increases the open-circuit voltage ofPETVT8-TBT based PSCs to 1.03 V, by both decreasing HOMO of the polymer and reducing the energy losses. Extending the intrinsic alkyl group resolved the problem of low solubility ofPETVT-TBT, and furthermore, was benefit to improve charge carrier mobility in the resulting polymer based solar cells. As a result, PETVT-TBT24 basically maintained the advantages of ETVT based photovoltaic polymers, realizing a moderate PCE of 7.8% when paired with the non-fullerene acceptor of ITIC. Graphical abstract: Image 1 Highlights: Ring Fusion of thiophene−vinylene−thiophene (TVT) benefits photovoltaic performance. Side chains play a prominent part in properties of the photovoltaic polymers. Longer side chain is good for charge carrier mobility but not good for morphology.